Penanaman Nilai-Nilai Agama Melalui Media Bermain Puzzle pada Anak Usia Dini - Tawaduddin Nawafilaty (Al Hikmah: Indonesian Journal of Early Childhood Islamic Education (IJECIE), 2017)
The aim of this research is to know the effect of puzzle play on the imparting of religious values in early childhood especially in children with vulnerable aged 4-5 years in Lamongan. This research uses pre-design eksmerimental with model one group pretest-posttest design. Subjects in this study were 15 children aged 4-5 years to be A group of children in ABA 1 Kindergarten in Lamongan. Data collection method used in this research is observation and documentation with data analysis technique in this research using wilcoxon level test. Based on the analysis of data obtained by using tiered sign test of wilcoxon obtained Thit <Ttabel (0 <25), so Ho is rejected and Ha is accepted. Thus, the research hypothesis "there is influence of playing puzzle to impart religious values in early childhood" is accepted.